Differential Effects of Camel Milk on Insulin Receptor Signaling – Toward Understanding the Insulin-Like Properties of Camel Milk - Abdulrahman, Abdulrasheed O.; Ismael, Mohammad A.; Al-Hosaini, Khaled; Rame, Christelle; Al-Senaidy, Abdulrahman M.; Dupont, Joëlle; Ayoub, Mohammed Akli (Frontiers in Endocrinology, 2016)
Previous studies on the Arabian camel (Camelus dromedarius) showed beneficial effects of its milk reported in diverse models of human diseases including a substantial hypoglycemic activity. However, the cellular and molecular mechanisms involved in such effects remain completely unknown. In this study, we hypothesized that camel milk may act at the level of human insulin receptor (hIR) and its related intracellular signaling pathways. Therefore, we examined the effect of camel milk on the activation of hIR transiently expressed in human embryonic kidney 293 (HEK293) cells using bioluminescence resonance energy transfer (BRET) technology. BRET was used to assess, in live cells and real-time, the physical interaction between hIR and insulin receptor signaling proteins (IRS1) and the growth factor receptor-bound protein 2 (Grb2). Our data showed that camel milk did not promote any increase in the BRET signal between hIR and IRS1 or Grb2 in the absence of insulin stimulation. However, it significantly potentiated the maximal insulin-promoted BRET signal between hIR and Grb2 but not IRS1. Interestingly, camel milk appears to differentially impact the downstream signaling since it significantly activated ERK1/2 and potentiated the insulin-induced ERK1/2 but not Akt activation. These observations are to some extent consistent with the BRET data since ERK1/2 and Akt activation are known to reflect the engagement of Grb2 and IRS1 pathways, respectively. The preliminary fractionation of camel milk suggests the peptide/protein nature of the active component in camel milk. Together, our study demonstrates for the first time an allosteric effect of camel milk on insulin receptor conformation and activation with differential effects on its intracellular signaling. These findings should help to shed more light on the hypoglycemic activity of camel milk with potential therapeutic applications.